Distinguishing the Multifunctional bound Morpheme from the Portmanteau morph in the Kurdish Language - Hussein, haval; Ali, Dilbrin (Humanities Journal of University of Zakho, 2022)
The research is tackled entitled “Distinguishing the Multifunctional bound Morpheme from the Portmanteau-morph in the Kurdish language”, since a hypothesis was made between them in the Kurdish language, and this study is dedicated to it. This term was mixed and used or interpreted below one phenomenon by Kurdish researchers and linguists. To know it, how to distinguish between these two terms and what is the reason that they were mixed by linguists. In order to get to know it more, to write about this title and apply the descriptive approach in it, searching to be done from the introduction and conclusion. The study is divided into four sections. In The first section, it deals with evaluating the previous researches on these two the two terms. The second section, the Multifunctional bound morpheme and its properties with the types of multifunctional at the level of bound morphemes that the restriction has been determined. The third section talks about the morph of the Portmanteau and its specificity. The fourth section distinguishes between a Multifunctional bond morpheme Pluralism and the Portmanteau morph. In the end, the study concluded that these two terms are completely different, and the main reason Its difference is due to the linguistic environment, because the Multifunctional bound morpheme can express many functions, including Inflectional and derivational in different environments. But the Portmanteau morph represents in one environment many Inflectional functions (morphemes).